Combined pyrotinib and fulvestrant for hormone receptor‐positive and HER2‐positive metastatic breast cancer: A multicenter, single‐arm, phase II trial - Jianli Zhao; Yunfang Yu; Wei Ren; Linxiaoxiao Ding; Yongjian Chen; Peng Yuan; Jian Yue; Yaping Yang; Guorong Zou; Tao Chen; Jie Chai; Li Zhang; et al. (MedComm)
Abstract This multicenter, single‐arm, phase II clinical trial (NCT04034589) evaluated the efficacy and safety of pyrotinib combined with fulvestrant in patients with HR‐positive/HER2‐positive metastatic breast cancer who had experienced trastuzumab treatment failure. A total of 46 patients were enrolled, receiving pyrotinib orally once daily and fulvestrant intramuscularly on days 1 and 15 of cycle 1, followed by monthly doses on day 1. The primary endpoint was progression‐free survival (PFS), while secondary endpoints included overall survival (OS), objective response rate (ORR), disease control rate (DCR), and safety. The median PFS was 18.2 months (95% CI, 11.9–31.1) overall, 19.5 months (95% CI, 10.6–NA) for those receiving the combination as first‐line therapy, and 18.4 months (95% CI, 16.7–NA) for patients with brain metastases. Median OS was not reached, with a 3‐year OS rate of 75.2% (95% CI, 62.8–90.2%). The ORR was 32.5%, and the DCR was 97.5%. Responses were observed in patients with low tumor mutation burden and ZNF217 mutation. Importantly, no grade 4 or higher treatment‐related adverse events or deaths were reported, indicating a favorable safety profile. In conclusion, the combination of pyrotinib and fulvestrant demonstrated promising antitumor activity and acceptable safety in HR‐positive/HER2‐positive metastatic breast cancer patients.